第54次日本南極地域観測隊東京海洋大学研究練習船「海鷹丸」（KARE16 - 北出, 裕二郎; キタデ, ユウジロウ; Kitade, Yujiro (国立極地研究所, 2016)
2012/2013年夏シーズンに，東京海洋大学研究練習船「海鷹丸」の海洋研究航海が，南大洋インド洋区で行われた．この航海では，東京海洋大学・国立極地研究所の連携事業として，文部科学省委託事業「南極地域観測事業基本観測」を実施したほか，両機関の共同研究として，日本南極地域観測第Ⅷ期計画（第52?57次隊）研究課題である「プランクトン群集組成の変動と環境変動との関係に関する研究」及び東京海洋大学・極地研究所共同研究「南大洋の環境変動と生態系変動」が実施された．海鷹丸は平成24年12月31日，フリーマントルを出港後，東経110度の海氷縁に及ぶ海域の観測を行い，平成25年1月24日，ホバート港へ寄港した．この間，海洋物理・化学観測では，海氷縁海域において海底直上までのCTD（Conductivity Temperature Depth profiler）観測が行われ，南極底層水の性質を精度高く観測することができた．また，プランクトン群集の定量的な鉛直分布を調べるため各種ネットによる曳網や南極底層水の動態を調べる長期係留系2系統の設置が行われた． A marine science cruise was undertaken in the Indian sector of the Southern Ocean during the 2012/2013 austral summer on the training vessel Umitaka-maru (KARE16; UM-12-08) of the Tokyo University of Marine Science and Technology (TUMSAT). A primary aim of the cruise was to carry out a TUMSAT and National Institute of Polar Research (NIPR) collaborative project commissioned by the Ministry of Education, Culture, Sports, Science and Technology (MEXT), entitled“Japanese Antarctic Research Expedition (JARE) Routine Observation: Physical and Chemical Oceanography”. In addition to the MEXT-commissioned project, two TUMSAT-NIPR collaborative projects were conducted: 1)“Studies on Plankton Community Structure and Environment Parameters in the Southern Ocean”, which is one of the original research projects of the JARE phase VIII (JAREs-52 to -57) projects; and 2)“Environment and Ecosystem Changes in the Southern Ocean”. The Umitaka-maru departed from Fremantle, Australia, on 31 December 2012, sailed to the study area situated along 110°E in the marginal sea ice zone, and returned to Hobart, Australia, on 24 January 2013. Detailed properties of the Antarctic bottom water were revealed from physical and chemical oceanographic observations collected using a conductivity-temperature-depth profiler deployed to near the seafloor in the marginal ice zone. In addition, participants performed various net castings to qualitatively evaluate the vertical distribution of plankton communities, and deployed two year-round mooring arrays to assess the dynamics of ...